2007
DOI: 10.1177/1359105307076232
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Adherence among Primary Care Patients in a Historically Disadvantaged Community in South Africa

Abstract: The present study examined the issue of treatment adherence among a sample of 23 rural South African patients living with either hypertension or diabetes, or both. The sample was asked to participate in qualitative interviews that asked about various aspects of their experience of their illness and treatment. The analysis of the data focused on the content of participants' concerns and difficulties with adhering to treatment recommendations. The themes that emerged from the study were participants' attribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 34 publications
5
47
0
Order By: Relevance
“…3 Moreover, interventions require an understanding of the social processes and cultural fabric that can create adherence differentials. 4,5 In South Africa, an estimated 50 per cent of those in need of ART receive treatment in the largest public sector treatment program (Department of Health Discussion Document, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…3 Moreover, interventions require an understanding of the social processes and cultural fabric that can create adherence differentials. 4,5 In South Africa, an estimated 50 per cent of those in need of ART receive treatment in the largest public sector treatment program (Department of Health Discussion Document, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Acyclovir is known to effectively reduce herpes symptoms (Lebrun-Vignes et al, 2007), so it is possible that some participants truly experienced fewer symptoms while taking acyclovir. Such a positive belief does not guarantee consistent, long-term adherence, particularly in settings in which people commonly believe that the disappearance of symptoms means cure (Kagee, Le Roux, & Dick, 2007;Plummer et al, 2006). Importantly, pill count adherence estimates in the trial overall were similar for acyclovir and placebo recipients (WatsonJones et al, 2008).…”
Section: Discussionmentioning
confidence: 87%
“…As displayed in the Figure, the multifaceted intervention facilitates bidirectional conversations between patients and health care providers through the IVR system. 9 The telehealth technology supports this process by providing patients with immediate feedback about home BP measurements and the opportunity to request follow-up calls from the pharmacist. Further, patients are able to see the benefits of diet, exercise, and/or medications through home BP monitoring, which reinforces the importance of these mediators to reduce BP.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,[22][23][24][25][26] Previous studies have concluded that an organized system of regular follow-up, a stepped-care approach to a patient's hypertension regimen, 27 and integration of computer technology can improve BP control. 28 However, the literature lacks a model that integrates these different components into an organized system that supports patient care on multiple levels, which is the foundation of our theoretical framework.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation